Direct and indirect effects of nesting density on survival and breeding propensity of an endangered shorebird. Issue 6 (3rd June 2019) - Catlin, Daniel H.; Gibson, Daniel; Hunt, Kelsi L.; Friedrich, Meryl J.; Weithman, Chelsea E.; Karpanty, Sarah M.; Fraser, James D.
Abstract: Density‐dependent regulation is a fundamental part of ecological theory and a significant driver of animal demography often through complex feedback loops. We investigated the relationship between flood‐ and demographically induced fluctuations in density and the breeding propensity and survival of a pioneer species, the piping plover (plover, Charadrius melodus ). We captured and marked adult and hatchling plovers on the Gavins Point Reach of the Missouri River in South Dakota and Nebraska, USA, from 2005 to 2014. In 2010 and 2011, historically high water levels and flooding inundated much of the plover's sandbar nesting habitat on the Missouri River. We developed a Bayesian formulation of a multievent model, or a multistate survival model with state uncertainty to estimate breeding propensity simultaneously with survival. Although plovers are conspicuous, their breeding status can be difficult to establish with certainty, which necessitated the use of uncertain states. With this model, we investigated the effect of sex, habitat availability, river flow, and density (birds/ha nesting habitat) on survival of hatch year and breeding and non‐breeding adult plovers. In addition, we estimated the transition rates for these age classes between breeding and non‐breeding states. Non‐breeding adults ( ϕ ¯ AHY, n  = 0.58 ± 0.06) had lower survival rates than breeding adults ( ϕ ¯ AHY, b  = 0.80 ± 0.04), and both breeding survival and breeding propensity decreased with increasing nesting density. Not only did survival and breeding propensity decrease directly at higher nest densities, but survival also was indirectly impacted by increasing the proportion of non‐breeding birds with relatively low survival. Thus, plovers were regulated through a complex set of feedback loops, acting as densities increased. Our findings underscore the intricacy of density‐dependent regulation and suggest that detailed demographic studies are needed to fully understand these effects.